Seed quality improvement with fruit extracts in blackgram - T, Poovarasan; S, Lakshmi; J, Renugadevi; A, Senthil (Journal of Phytology, 2019)
The present study was conducted to know the effect of extracts from parts of papaya and pomegranate fruits containing enormous amount of antioxidants on the seed quality parameters of blackgram (Vigna mungo L.). Blackgram seeds were soaked in papaya peel, pulp, seeds and pomegranate peel, seeds extracts viz., 2.5 %, 5 %, 7.5 % and 10 % concentration for 1 hour. The physiological parameters were evaluated under laboratory conditions. The results revealed that seeds treated with 2.5 % papaya seed extract recorded high physiological and biochemical changes in terms of field emergence, germination percentage, seedling length, dry matter production, vigour index and ?- amylase activity when compared to rest of treatments and control.